Module 3: Pedagogy - Wan Yusoff, Wan Mazwati (2021)
This module focuses on theory and methods of teaching. Pedagogy is the “art, science, or profession of teaching; especially in education” (Merriam-Webster Dictionary). From this definition, it can be deduced that pedagogy is multidimensional. But in a nutshell, pedagogy is about studying teaching methods. Studying teaching methods is not limited to designing how to deliver lesson plans but also includes multi-faceted aspects that make teaching and learning processes effective and meaningful. This unit exposes teachers to learning theories, learning styles, teaching styles, teacher feedback, assessment and many more. This module presents only the first part of pedagogy which are a concept of pedagogy, learning theories and the importance of learning theories for effective teaching.